Pengembangan Modul IPA Biologi Terintegrasi Iman dan Taqwa (IMTAQ) Pada Materi Pencemaran Lingkungan Siswa Kelas VII SMP Negeri 1 Bajeng - Mirdawati, Mirdawati; Ismail, Ilyas; Hamansah, Hamansah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study aimed to develop a science and biology module integrating the values of faith and piety (IMTAQ) and to evaluate its validity, practicality, and effectiveness in the learning process. The module was developed using the 4-D model, which comprises four stages: define, design, develop, and disseminate. The field trial involved 27 seventh-grade students at SMP Negeri 1 Bajeng. Data were collected using validation sheets, student response questionnaires, and learning achievement tests. Data analysis focused on assessing the validity, practicality, and effectiveness of the developed product. The findings demonstrated that the module achieved a high level of quality. The mean validation score of 3.81 indicated that the module was highly valid, while the mean student response score of 3.64 showed that it was highly practical for instructional use. Furthermore, all students achieved learning mastery, resulting in a 100% mastery rate and indicating that the module was highly effective. Based on these findings, the IMTAQ-integrated science and biology module was considered suitable for use as instructional material because it met the criteria for validity, practicality, and effectiveness.